Graves' Disease and Diabetes Mellitus - M. Suttan Assin; Jusuf Rukman; Jose R. L. Batubara; Purnama Wati S. P. (Indonesian Pediatric Society, 1992)
Thyroid hormones play an important role in the metabolic propesses. Its disturbances will involve several organs, consequently. A 5 year old girl with Graves' diseases, after several weeks of treatment with propylthiouracil (PTV), developed thyrotoxicosis crisis and diabetes mellitus with ketoacidosis; a condition which is usually fatal. Treatment toward the hyperthyroid state overcome the diabetic stage, eventually. This report is an example of an endocrinological interaction in a hyperthyroid patient. Therefore, the diabetogenic effect of hyperthyroxinemia should not be overlooked.